1991
DOI: 10.1055/s-2007-1003750
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor I (IGF-I) and Insulin Binding to Erythrocytes of Normal Prepubertal Children and Adults

Abstract: Erythrocyte insulin-like growth factor I (IGF-I) and insulin receptors were characterized in 10 normal prepubertal children (5 girls and 5 boys) aged 4-11 yrs and 10 normal adults (4 women and 6 men) aged 32-47 yrs. erythrocytes were purified from 5 ml of blood by Ficoll-Paque gradient centrifugation. Reticulocytes count in the erythrocyte suspensions were lower than 1%. Insulin and IGF-I binding assays were performed simultaneously. Maximal percent binding of [125I] labelled IGF-I was significantly higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

1993
1993
1997
1997

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…The results of this study demonstrate that women with PCOS have an increased number of IGF-I receptors on erythrocytes in comparison to normo-ovulatory women. Although the mature erythrocyte has no nucleus it reflects the intrinsic genetic programming of the primary cell and previous insulin and IGF-I binding studies have shown that it is an acceptable tissue for evaluating changes in receptor concentration and affinity (Geffner et al, 1987;Ward, 1988;Dooghe et al, 1991;Eshet et al, 1993). Unlike previous studies, demonstrating that IGF-I regulates its own receptor on erythrocytes (Eshet et al, 1991(Eshet et al, , 1993Hochberg et al, 1992), we found no difference in serum IGF-I levels between PCOS and controls, both being within the normal range.…”
Section: Discussioncontrasting
confidence: 78%
“…The results of this study demonstrate that women with PCOS have an increased number of IGF-I receptors on erythrocytes in comparison to normo-ovulatory women. Although the mature erythrocyte has no nucleus it reflects the intrinsic genetic programming of the primary cell and previous insulin and IGF-I binding studies have shown that it is an acceptable tissue for evaluating changes in receptor concentration and affinity (Geffner et al, 1987;Ward, 1988;Dooghe et al, 1991;Eshet et al, 1993). Unlike previous studies, demonstrating that IGF-I regulates its own receptor on erythrocytes (Eshet et al, 1991(Eshet et al, , 1993Hochberg et al, 1992), we found no difference in serum IGF-I levels between PCOS and controls, both being within the normal range.…”
Section: Discussioncontrasting
confidence: 78%
“…It has since been clearly demonstrated not only that erythroid progenitor cells respond to stimulation by IGF-I, indicating the presence of IGF-I receptors (Geffner et al, 1987), but also that erythrocytes (RBC) originating from these cells have specific IGF-I receptors (Polychronakos et al, 1983). Because it is easy to obtain a large number of RBC from small volumes of blood, they are now being used in clinical investigations (Hizuka et a!., 1985;Catanese et al, 1986;Izumi et a!., 1986;Dooghe et al, 1991). Eshet et al (1991;1993) recently demonstrated that there is an increase in IGF-I binding sites on RBC and increase in mRNA of IGF-I receptor in lymphocytes of patients with chronic low IGF-I serum concentrations.…”
mentioning
confidence: 99%